2010
DOI: 10.1071/en09144
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between atmospheric organic compounds and air-mass exposure to marine biology

Abstract: Environmental context.The exchange of gases between the atmosphere and oceans impacts Earth’s climate. Over the remote oceans, marine emissions of organic species may have significant impacts on cloud properties and the atmosphere’s oxidative capacity. Quantifying these emissions and their dependence on ocean biology over the global oceans is a major challenge. Here we present a new method which relates atmospheric abundance of several organic chemicals over the South Atlantic Ocean to the exposure of air to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 66 publications
(77 reference statements)
3
41
0
Order By: Relevance
“…We found a weak positive correlation between the AMS organics and fluorometer measurements for the VOCALS campaign (r = 0.35), but no relationship for OOMPH. Recent work demonstrated the importance of accounting for the air mass history when analyzing the variability in atmospheric tracers (Arnold et al, 2010). We found a marginal improvement in correlation between the organics and chlorophyll-a, when the latter was averaged over 2-day back-trajectories.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…We found a weak positive correlation between the AMS organics and fluorometer measurements for the VOCALS campaign (r = 0.35), but no relationship for OOMPH. Recent work demonstrated the importance of accounting for the air mass history when analyzing the variability in atmospheric tracers (Arnold et al, 2010). We found a marginal improvement in correlation between the organics and chlorophyll-a, when the latter was averaged over 2-day back-trajectories.…”
Section: Resultsmentioning
confidence: 71%
“…Alvain et al (2005) has identified the major dominant phytoplankton functional types from SeaWiFS measurements. The degree of correlation between atmospheric tracers and exposure to chlorophyll-a has been shown to be dependent on these types (Arnold et al, 2010). Recent work by Fuentes et al (2010) has further shown that the relationship between chlorophyll-a and organic mass fraction in aerosols are expected to be very complex, as seawater OM production by marine biota depends on conditions in the algal blooms, including nutrient availability, temperature and lifespan of algal cells.…”
Section: Resultsmentioning
confidence: 99%
“…The PHYSAT approach relies on the identification of specific signatures in the normalized water leaving radiance (nLw) spectra measured by an ocean color sensor (Alvain et al, , 2008, thereby enabling the identification of nanoeukaryotes, haptophytes (a major component of the nanoflagellates), Synechococcuslike cyanobacteria, diatoms, Prochlorococcus, Phaeocystis-like phytoplankton, and coccolithophorids. The PHYSAT method has been successfully validated with phytoplankton in situ data and extensively used by many authors (e.g., Bopp et al, 2005;Arnold et al, 2010;D'Ovidio et al, 2010;Gorgues et al, 2010;Masotti et al, 2010Masotti et al, , 2011Alvain et al, 2012Alvain et al, , 2013Belviso et al, 2012;Demarcq et al, 2012;De Monte et al, 2013;Hashioka et al, 2013;Ben Mustapha et al, 2014;Thyssen et al, 2015). Navarro et al (2014) later proposed a regionalized version of the algorithm for the Mediterranean Sea (Figure 1), the PHYSAT-Med, using the MODIS era (2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013) for identification of nanoeukaryotes, Prochlorococcus, Synechococcus-like cyanobacteria and diatoms, which was compared with more than 3,000 high-performance liquid chromatography (HPLC) in situ measurements (see Table 3 in Navarro et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…[]). Laboratory and field data exist, linking very short‐lived iodocarbons and phytoplankton activity [ Smythe‐Wright et al ., ; Hill and Manley , ; Arnold et al ., ; Brownell et al ., ; Lai et al ., ]. However, there is increasing evidence that biological sources of iodine precursors are not the most significant [ Garland and Curtis , ; Reeser et al ., ; Martino et al ., ; Sakamoto et al ., ; Mahajan et al ., ].…”
Section: Introductionmentioning
confidence: 99%